Iterative learning control for vacuum heat treatment process - Balik, Piotr; Klimkowicz, Kamil; Patan, Maciej (1975- )
Distributed parameter systems constitute an important class of modern industrial processes. However, in many practical applications the engineers still tend to adapt some classical control techniques developed for lumped systems totally neglecting the spatial dynamice of investigated process. In a view of increasing demands imposed on system accuracy and performance such conventional control algorithms simply become insufficient and there is a great necessity for novel identification and control methods taking into account both the temporal and spatial dynamics.
Keywords: iterative learning control; batch processes